Analisis Determinan Firm Value dengan Model Rasio Tobin's Q: Studi Empiris di Indonesia - Gama, Veronicha Maria Jona Chin Shiet Fa; Thomas Averio (Forum Kerjasama Pendidikan Tinggi, 2025)
The basic materials sector has unique characteristics because it requires large amounts of capital, depends heavily on natural resources, and faces strong exposure to environmental issues. These conditions make the factors that influence firm value in this sector more varied and sensitive to both financial and non-financial changes. This study examines the “effect of tax avoidance, green accounting, institutional ownership, leverage, and profitability on firm value in basic materials companies listed on the Indonesia Stock Exchange during 2020–2024”. This research uses a quantitative approach with multiple linear regression, processed using IBM SPSS Statistics version 26. The t-test results show that green accounting, leverage, and profitability have a positive effect on firm value, while tax avoidance and institutional ownership have a negative effect. The Adjusted R Square value of 0.891 indicates that the model explains 89.1% of the variation in firm value. In addition, the F-test shows a significance value of 0.00 < 0.05, meaning the model is appropriate to use. Overall, the findings show that firm value in the basic materials sector is strongly influenced by sustainability practices, ownership structure, and financial performance.